'Turn‐off' fluorescence strategy for determination of hexavalent chromium ions based on copper nanoclusters. (4th September 2020) - Cao, Xueling; Bai, Yageng; Liu, Faxian; Li, Fei; Luo, Yanan
Abstract: Cu nanoclusters (CuNCs) capped by tannic acid (TA) (CuNCs@TA) can be used as a highly sensitive fluorescent probe for Cr(VI) detection. Therefore, a fluorescence detection method for Cr(VI) can be established according to the fluorescence quenching of CuNCs@TA that is caused immediately after the addition of Cr(VI). The fluorescence quenching efficiency of CuNCs@TA was linearly correlated with Cr(VI) concentration within the range 0.03–60 μM, and the detection limit for Cr(VI) was 5 nM. This method was demonstrated to be suitable for detecting Cr(VI) in actual water samples. We found that sodium thiosulfate (ST) can redox with Cr(VI) and therefore restore the fluorescence of CuNCs@TA. The mechanism of CuNCs@TA fluorescence quenching and enhancement by Cr(VI) and ST was investigated in detail. The 'turn‐on' fluorescent sensor is of practical significance and has broad application prospects. Abstract : The fluorescence quenching of CuNCs@TA was caused by the change in TA structure, and the method for detecting Cr (VI) by CuNCs@TA based on the "turn‐off" sensor was established. With the increase in the concentration of reducing ST, the highly oxidized Cr (VI) reacted with ST in an oxidation‐reduction reaction, and Cr (VI) separated from the CuNCs@TA surface. Thus, its fluorescence "turn on" sensor appeared.